Dynamics of Cardiac Autonomic Responses During Hemodialysis Measured by Heart Rate Variability and Skin Sympathetic Nerve Activity: The Impact of Interdialytic Weight Gain - Zhang, Yike; Wang, Jing; Xing, Yantao; Cui, Chang; Cheng, Hongyi; Chen, Zhenye; Chen, Hongwu; Liu, Chengyu; Wang, Ningning; Chen, Minglong (Frontiers in Physiology, 2022)
Background: Autonomic nervous regulation plays a critical role in end-stage kidney disease (ESKD) patients with cardiovascular complications. However, studies on autonomic regulation in ESKD patients are limited to heart rate variability (HRV) analysis. Skin sympathetic nerve activity (SKNA), which noninvasively reflects the sympathetic nerve activity, has not been used in ESKD patients. Methods: Seventy-six patients on maintenance hemodialysis (MHD) treatment (a 4-h HD session, three times a week) were enrolled. Utilizing a noninvasive, single-lead, high-frequency recording system, we analyzed the dynamic change in HRV parameters and SKNA during HD. The different characteristics between the subgroups divided based on interdialytic weight gain (IDWG, <3 kg or ≥3 kg) were also demonstrated. Results: After the HD, values for heart rate (75.1 ± 11.3 to 80.3 ± 12.3 bpm, p < 0.001) and LF/HF (1.92 ± 1.67 to 2.18 ± 2.17, p = 0.013) were significantly higher than baseline. In subgroup analysis, average voltage of skin sympathetic nerve activity (aSKNA) in IDWG ≥3 kg group was lower than the IDWG <3 kg group at the end of MHD (1.06 ± 0.30 vs 1.32 ± 0.61 μV, p = 0.046). Moreover, there was a linear correlation between mean heart rate (HR) and aSKNA in low IDWG patients (p < 0.001), which was not found in high IDWG patients. At the 1-year follow-up, high IDWG patients had a higher incidence of cardiovascular hospitalization (p = 0.046). Conclusions: In MHD patients, a gradual activation of sympathetic nerve activity could be measured by HRV and aSKNA. A lower aSKNA at the end of HD and a loss of HR-aSKNA correlation in overhydrated patients were observed. Extensive volume control is promising to improve the autonomic nervous function and clinical outcomes in this population.